Mechanical characterization of co-extruded short fiber reinforced thermoplastic with UV curable thermoset - Zhao, Zhilong (Nanyang Technological University, 2024)
In today’s manufacturing industry, carbon fiber has become a significant research focus due to its out standing physical properties. Short carbon fiber is particularly popular for its excellent performance and low processing costs. However, despite advancements in 3D printing with Short Carbon Fiber Reinforce ment (SCFR), limitations like porosity and poor interlaminar bonding still constrain its applications. As carbon fiber increasingly replaces traditional metal alloys, enhancing SCFR could unlock more potential, leading to new, high-value carbon fiber products. Current research mainly focuses on pure thermoplas tics or thermosets, with limited exploration of their blends. Blending these materials could leverage their strengths, offering enhanced performance and broader functionalities. This research aims to combine SCFR with UV Resin to create a superior material, SCFR-Epoxy, optimizing and overcoming traditional SCFR limitations for more advanced carbon fiber materials. Common 3D printers typically use materials that are purely liquid, solid, or powder, sometime they can also adapted into composite printing. To achieve good printed quality of these different materials, many printing method has been developed for rapid prototyping and fabrication of composite. Due to the unique composition of SCFR-Epoxy, which includes a solid component of carbon fiber and a liquid component of UV Resin, it cannot be directly printed using traditional printers. This project compiles common 3D printing methods to select the most suitable one for SCFR-Epoxy, and designs a detailed nozzle for the printing process. A 3D printer was built based on this design, and SCFR-Epoxy samples were manufactured. The project focuses on nozzle development, structure design, and parameter optimization. After nozzle characterization, tests were conducted to determine optimal printing parameters and fabricate samples for further testing. This analysis helps understand the ma terial’s properties and supports future research to develop enhanced composite materials with broader industrial applications.